2014
DOI: 10.1038/srep07102
|View full text |Cite
|
Sign up to set email alerts
|

Formation of quantum spin Hall state on Si surface and energy gap scaling with strength of spin orbit coupling

Abstract: For potential applications in spintronics and quantum computing, it is desirable to place a quantum spin Hall insulator [i.e., a 2D topological insulator (TI)] on a substrate while maintaining a large energy gap. Here, we demonstrate a unique approach to create the large-gap 2D TI state on a semiconductor surface, based on first-principles calculations and effective Hamiltonian analysis. We show that when heavy elements with strong spin orbit coupling (SOC) such as Bi and Pb atoms are deposited on a patterned … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 46 publications
(63 reference statements)
2
87
0
Order By: Relevance
“…Finally, we discuss the possibility of experimentally realizing these novel two dimensional materials. For materials like Pb, it has been theoretically demonstrated that substrates like SiH (111) [14][15][16] can be used as an effective tool to filter the p z orbitals to create a large gap topological insulator based on the p x,y orbitals. In addition, high quality thin films of Pb have been experimentally grown on insulating substrates using the molecular beam epitaxial technique [40], thus opens up the possibility to integrate conventional growth technology to produce large gap QSHI with p-orbitals.…”
Section: B Hydrogenation In 4d and 5d Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we discuss the possibility of experimentally realizing these novel two dimensional materials. For materials like Pb, it has been theoretically demonstrated that substrates like SiH (111) [14][15][16] can be used as an effective tool to filter the p z orbitals to create a large gap topological insulator based on the p x,y orbitals. In addition, high quality thin films of Pb have been experimentally grown on insulating substrates using the molecular beam epitaxial technique [40], thus opens up the possibility to integrate conventional growth technology to produce large gap QSHI with p-orbitals.…”
Section: B Hydrogenation In 4d and 5d Materialsmentioning
confidence: 99%
“…Figs. 6a and 6b Pb is patterned on SiH [14][15][16]. Thus, hydrogen is added to the two W atoms on one side of the thin film to filter out the d 3z 2 -r 2 at the Fermi level.…”
Section: B Hydrogenation In 4d and 5d Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…So the newly observed ( √ 3× √ 3) surface in heteroepitaxial Si(111) thin films is a big surprise, because it is fundamentally different from all the previous models, especially considering the unusual planar ring structure unexpected for Si. Clarifying the physical mechanism of such a unique surface reconstruction is thus of particular importance, which may profoundly renew our interest in Si surface and open a new route to realizing Dirac and topological bands in Si surface [30][31][32][33], as an interesting alternative to silicene.…”
mentioning
confidence: 99%